Clinical Profile of Kawasaki Disease (KD) in Children admitted at Dhaka Shishu Hospital (Northern International Medical College Journal, 2017)
Background : Kawasaki disease (KD) is an acute, febrile, self-limiting vasculitis of the medium-and small-sized arteries of unknown etiology. Recently its incidence is increasing worldwide.Objective : The aim of this study was to evaluate its presenting symptoms, clinical features and laboratory tests for the diagnosis of complete and incomplete KD in children.Materials & Methods : Medical records of 20 children with KD admitted in Dhaka Shishu Hospital from January, 2011 to December 2014, were reviewed. Demographic features, diagnostic clinical features of KD, and additional clinical findings including arthritis and/or arthralgia, gastrointestinal symptoms, respiratory symptoms and central nervous system symptoms were recorded for each patient. Besides, available laboratory findings collected on admission before Intravenous Immunoglobulin (IVIG) administration were reviewed. The diagnosis of complete and incomplete KD was made using the American Heart Association (AHA) recommendations.Results : About two-thirds of the children (65%) were 30 60 months, 20% were < 30 months and 15% were 60 or above 60 months old with mean age being 42 months. Over half (55%) of the children were female and 50% affected in summer season. Of the five principal signs, polymorphous skin rash was predominant (90%), followed by changes in oral mucosa or lip (85%), conjunctival hyperemia (75%), cervical lymphadenopathy (70%) and changes in distal extremities and gastrointestinal symptoms (each 65%). Majority of the children had raised WBC (75%), raised ESR (95%), increased platelet count (70%) and elevated CRP (75%). Uveitis was a predominant complication (45%), followed by facial paralysis (30%) and neurosensory hypoacusia (20%). Cardiovascular complications were less commonly found (30%). Neither age nor sex was found to be associated with type of Kawasaki disease (p = 0.450 and p = 0.535 respectively). Sixty percent of the patient fulfilled the criteria of complete KD and the rest incomplete KD. However, cervical lymphadenopathy and changes in distal extremity were significantly common in complete KD than those in incomplete KD (p = 0.019 and p = 0.05 respectively).Conclusion : In this study 60% of the patient fulfilled the criteria of complete KD and the rest incomplete KD.Northern International Medical College Journal Vol.8(2) January 2017: 216-219